Murcybolus gen. nov., a new net-winged beetle genus from mid-Cretaceous Burmese amber (Coleoptera: Lycidae: Burmolycini) - Li, Yan-Da; Tihelka, Erik; Huang, Diying (Zootaxa, 2021)
A new lycid beetle, Murcybolus longiantennus gen. et sp. nov., is reported from mid-Cretaceous Burmese amber (ca. 99 Ma). Murcybolus is placed in the recently erected fossil tribe Burmolycini based on the fully metamorphosed female, 10-segmented antennae, and pronotal disc with deep rounded punctures but without carinae. Murcybolus differs from the other genus in Burmolycini, Burmolycus, by its antennal morphology and elytral venation.